Influence of Training on Employees' Performance in Service Sector of Nepal - Khati, Prem Bahadur (The Management Review, 2026)
Training plays a significant role in improving employee skill, knowledge and overall productivity. This research inquiries about the influence of training on employee performance in service sector of Nepal focusing into four aspects: training design, effectiveness of training, frequency to training and On-the-job training methods. This study uses a quantitative research design where primary data were collected using a questionnaire from 315 employees working in the banking, education, health and hospitality industries. The statistics were descriptive, and included Pearson's correlation, multiple linear regression analysis as well as one way ANOVA. The results further showed that all training dimensions have a positive and significant effect on employee performance. On-the-job training proved to be the most powerful predictor, followed by training effectiveness, training frequency and training design. Correlation analysis also provides support that significant positive correlations exist between different of training and employee performance. But the ANOVA test results show that there are no differences in employee performance by type of service among the service industries, leaving unchanged the relationship between training and men's productivity by industry. The results are consistent with the Human Capital Theory and support the argument that intentional investments in training may positively influence employee performance in Nepalese service industries. The research has useful implications for managers and policy-makers and highlights the importance of quality, regular, on-the-job training in enhancing employee performance.